Convection-diffusion Model For Alumina Concentration in Hall-Héroult Process*. Issue 21 (2022) - Moreira, Lucas José da Silva; Besançon, Gildas; Ferrante, Francesco; Fiacchini, Mirko; Roustan, Hervé
Abstract: Hall-Héroult process is an electrolysis method to produce aluminum at industrial scale. It is based on an electrochemical reaction that requires an alumina dissolution in a bath solution. The hazardous operational conditions make it difficult the development of a sensor for continuous measurement. Moreover, local variations of alumina concentration throughout the pot cell arise during daily operations. This paper presents a modeling procedure to obtain a spatio-temporal dynamic representation of alumina concentration distribution. From the convection-diffusion relations, the alumina source term is analyzed and expanded to obtain the relations between the available signals and the output. The goal is to develop a system that is able to predict the obtained measurement by taking into account transport properties. The model is validated with industrial data and compared with other models.